Distinguishing Characteristics of Benign Versus Malignant Intraosseous Schwannomas: A Comparative Study - Jiangchao Zhang; Ge Xiong; Wei Zheng; Jing Sun (Orthopaedic Surgery)
ABSTRACT Objectives Benign and malignant intraosseous schwannomas are rare, and primarily documented in case reports. This study aims to elucidate the differences in clinical features and imaging manifestations between these tumors. This will help clinicians identify malignant lesions at an early stage, reliable guide treatment decisions, and accurately predict outcomes. Methods Eighteen patients who underwent surgery and got pathological examinations in our hospital from 2012 to 2023 were retrospectively reviewed. Among them, 14 cases were found benign with 4 malignant. In the benign group, patients underwent curettage followed by bone grafting, whereas the malignant group was treated with extensive resection or amputation. Patients' demographics and radiographic features, including gender, age at diagnosis, symptom duration, tumor location, tumor margin, and the ratio of sclerotic margins were documented and compared between these tumors. All imaging was reviewed by two fellowship‐trained musculoskeletal radiologists, who also quantified the sclerotic margin ratio. The intraclass correlation coefficient was used to determine inter‐observer agreement. The Mann–Whitney U test was applied for continuous clinical variables, and the chi‐square test or Fisher's exact test for categorical variables. Results In our series, the mean age of these patients was 43.1 ± 14.0 years, six patients were male and 12 were female. Pain was the predominant preoperative symptom. The average duration from symptom onset to initial physician visit was 28.5 ± 25.3 months for benign schwannomas and 8.3 ± 4.3 months for malignant schwannomas (p = 0.012). On plain radiographs, 13 (13/14) of benign schwannomas exhibited well‐defined margins of bone destruction, compared to 1 (1/4) of malignant schwannomas (p = 0.019). Furthermore, benign schwannomas had a significantly higher sclerotic margin ratio (75.5%) than malignant ones (16.7%) (p = 0.001). No statistically significant difference was found between the two groups in terms of cortical bone destruction (p = 1.0). On MRI, both tumors demonstrated intermediate to slightly hypointense signal intensity on T1‐weighted images and heterogeneous high signal intensities on T2‐weighted images. Conclusions Despite their rarity, benign and malignant intraosseous schwannomas should be considered in the differential diagnosis for patients presenting with painful and radiographically lytic bone lesions, especially in the mandible, sacrum, and vertebrae. The ratio of sclerotic margins, which we proposed for the first time, in combination with symptom duration and the clarity of tumor margins, provide valuable diagnostic clues for distinguishing the malignancy of the tumors.